Indicators of Mental image among Students of the University of Baghdad about Iraqi Political Parties-(a research based on a master thesis) - موحان نور اختياري; جاسم باقر موسى (ALBAHITH ALALAMI, 2016)
Media studies have focused mostly on the issue of the mental image because the image that is formed in the mind has become not only a photo of a human being and having kept for himself. This image has an outside influence which may sometimes up to the formation of the fate of others and it sometimes includes individuals and groups together. This study comes in the context of identifying the image of Iraqi political parties among Iraqi university students and the nature of the view that students have in their minds about these parties. Chapter one includes the problem of the research, the importance of the study, the goals and method used. Chapter two is divided into two sections: section one deals with the concept of the mental image and its components; section two is about the concept of political parties, their elements, and classifications; section three discusses the title ‘the effectiveness of the function of public relations in the concept and aims of public parties. Chapter three is about a field study.